Analysis of Financial Feasibility of Anchovy Business (Stolephorus sp) Using Bagan Tancap in Muara Nibung Village, Pandan District, North Sumatra Province - Tio Afandi Nasution; Zulkarnaini Zulkarnaini; Hendrik Hendrik (Jurnal Perikanan dan Kelautan, 2023)
This research was conducted in Muara Nibung Village, Pandan District, Central Tapanuli Regency, North Sumatra Province with the aim of knowing the amount of investment, profits, and the level of feasibility of fishing for a tancap fisherman based on financial (financial) aspects using investment analysis, income, profit, revenue cost (R/C), financial rate of return (FRR), and payback period of capital (PPC). The method used in this study is a survey method while the determination of respondents is carried out by census. Data collection was carried out by observation, interviews, and documentation directly with 37 people of bagan tancap fishermen. The results of the study show that the step-by-step chart in Muara Nibung has two categories of operating distance from the coast, including the near chart ±1 km and the far chart ±3 km, of course, different investments, profit, and business feasibility. For charts close to ±1 km the total investment is (Rp124.616.000,00), the profit received is (Rp121,240,800.00/year), R/C (2.59), FRR (97.29), PPC (1.03). Whereas Forfar chart ±3 km the total investment is (Rp139,416,000.00), the profit received is (Rp179,140,800.00/year), R/C(2.85), FRR (128.49), PPC (0.78). Based on the results of the calculation that the R/C is more than 1, the FRR is greater than the bank interest rate of 11%, and the PPC is getting smaller, meaning that the fishing business is profitable and feasible to continue